Advances in parasitology. Volume 36 - Muller, R.; Baker, J. R.; Rollinson, D. (London ; New York : Academic Press, 1995)
Advances in Parasitology is a series of up-to-date reviews of all areas of interest in contemporary parasitology. It includes medical studies on parasites of major influence, such as typanosomiasis and scabies, and more traditional areas, such as zoology, taxonomy, and life history, which shape current thinking and applications.
21. Animals lmplicated as Reservoirs of Lyme Disease22. Incompetent/Non-susceptible (Though Often Antibody Positive); 23. Spirochaetes per Tick; 24. How Ticks are Infected; 25. Monitoring the Cycles; 26. Complex Modelling; 27. Risk Assessment; 28. Spatial Assessment; 29. Prevention; 30. Vaccination; References; Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Parasitology; Parasitism; Parasitic diseases -- Periodicals; Parasitology -- Periodicals; Parasitology; MEDICAL -- Parasitology; Parasitism; Parasitology; Electronic books